El género Cunila (Lamiaceae, Mentheae) en Argentina - Xifreda, Cecilia Carmen (2006)
Cunila is an American genus with about 23 species and a disjunctive distribution between the United States of America (from New York State to Texas and Florida) and Central America, and Southern Brazil, south of Uruguay and NE Argentina. Four species of Cunila (C. angustifolia, C. incana, C. microcephala and C. spicata) were recorded for Argentina, with an area of distribution ranging from Misiones to Santa Fe provinces. This contribution is a systematic review of this genus in Argentina, including descriptions, synonymies, new lectotypification, and a key to species. Morphological information and iconography of C. incana and C. spicata are provided. The area of distribution for Cunila microcephala is extended 4 degrees West (ca. 62° Long. W), up to Santa Fe province, Castellanos department.